2020
DOI: 10.1037/xge0000785
|View full text |Cite
|
Sign up to set email alerts
|

Core cognition in adult vision: A surprising discrepancy between the principles of object continuity and solidity.

Abstract: From an early age, humans intuitively expect physical objects to obey core principles, including continuity (objects follow spatiotemporally continuous paths) and solidity (two solid objects cannot occupy the same space at the same time). These two principles are sometimes viewed as deriving from a single overarching "persistence" principle. Indeed, violations of solidity where one solid object seemingly passes through another could theoretically be interpreted as a violation of continuity, with an object "tel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, recent studies with adults using variations on infant VOE experiments reveal converging results across ontogeny in a range of domains of knowledge (e.g. Kominsky et al, 2021;Falck et al, 2020;Schurgin & Flombaum, 2017;Strickland & Scholl, 2015;van Marle & Scholl, 2003). For example, infant VOE studies have revealed that infants use objects' width, but not objects' height, to reason about whether an object can be fully hidden inside a container (Baillargeon, 2008;Hespos & Baillargeon, 2001).…”
Section: The Violation-of-expectation Methods Reveals Continuity Acro...mentioning
confidence: 99%
“…Furthermore, recent studies with adults using variations on infant VOE experiments reveal converging results across ontogeny in a range of domains of knowledge (e.g. Kominsky et al, 2021;Falck et al, 2020;Schurgin & Flombaum, 2017;Strickland & Scholl, 2015;van Marle & Scholl, 2003). For example, infant VOE studies have revealed that infants use objects' width, but not objects' height, to reason about whether an object can be fully hidden inside a container (Baillargeon, 2008;Hespos & Baillargeon, 2001).…”
Section: The Violation-of-expectation Methods Reveals Continuity Acro...mentioning
confidence: 99%
“…Motion trajectories across perceptual gaps are perceived to be valid when the object's position after the gap is consistent with the physical motion trajectory observed before the gap. However, when an object after occlusion reappears in an unexpected position or at an unexpected time, object continuity is interrupted [67][68][69][70][71][72]. This highlights that the predicted motion trajectory is integrated with the physical motion after the gap.…”
Section: The Phenomenology Of Perceptual Gapsmentioning
confidence: 99%